2011
DOI: 10.1002/nml.20032
|View full text |Cite
|
Sign up to set email alerts
|

Nonprofit watchdogs: Do they serve the average donor?

Abstract: Nonprofit watchdog organizations-organizations devoted to rating the accountability and transparency of nonprofits-claimI N AN IDEAL world, all of the information necessary to compare nonprofits would be available to potential donors. If this were the case, the best nonprofits-those that produce the most public goods and that act the most effectively and ethically-would attract the most donations, and the rest would perish. However, comprehensive comparative information does not exist, and donors must accept t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
61
1
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(65 citation statements)
references
References 22 publications
1
61
1
2
Order By: Relevance
“…In recent years a number of third‐party accountability systems have been developed in order to increase public perceptions of accountability in the nonprofit sector and to reduce the degree of information asymmetry that occurs in donative transactions; and, several scholars have begun examining whether these accountability systems have any impact on donor behavior (see, for instance, Cnaan et al ; Gordon et al ; Sloan ). For the most part, findings from these studies have shown that these accountability systems are not frequently utilized in the donor decision‐making process (Cnaan et al ; Silvergleid ). However, the findings from this study indicate that many of these studies may have overlooked an important possibility, that is, some individuals may be more likely than others to turn to third‐party accountability systems when seeking to obtain information on nonprofit performance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years a number of third‐party accountability systems have been developed in order to increase public perceptions of accountability in the nonprofit sector and to reduce the degree of information asymmetry that occurs in donative transactions; and, several scholars have begun examining whether these accountability systems have any impact on donor behavior (see, for instance, Cnaan et al ; Gordon et al ; Sloan ). For the most part, findings from these studies have shown that these accountability systems are not frequently utilized in the donor decision‐making process (Cnaan et al ; Silvergleid ). However, the findings from this study indicate that many of these studies may have overlooked an important possibility, that is, some individuals may be more likely than others to turn to third‐party accountability systems when seeking to obtain information on nonprofit performance.…”
Section: Discussionmentioning
confidence: 99%
“…In fact after several well‐publicized scandals during the 1980s and 1990s public calls for greater accountability in the nonprofit sector led to the emergence of a number of nonprofit “watchdog organizations,” such as Charity Navigator the Better Business Bureau's Wise Giving Alliance and the American Institute on Philanthropy (Chen ; Chhaochharia and Ghosh 2; Silvergleid 11). Because most people have limited information about how nonprofits operate these watchdog organizations were created with the expectation that they would provide both donors and potential donors with unbiased and easily accessible accountability information so that they might make better “educated decisions about where to donate money” (Cnaan Jones Dickin and Salomon 381)…”
mentioning
confidence: 99%
“…First, volunteering is inconsistently measured (Cnaan, Jones, Dickkin, & Salomon, 2011). No established framework for differentiating volunteer domains exists, in part, because the studies that do define volunteering do not provide a consistent categorization.…”
Section: Limitations In Existing Researchmentioning
confidence: 99%
“…Upon accepting the contract and expecting a (unique) equilibrium gift g o from each solicitation, 17 the professional solicits n donors to maximize his profit:…”
Section: Outsourcing With Aware Donors: Near Impossibilitymentioning
confidence: 99%